(3VhGHW ef Yde GdChbGas ((3HdOg GdSeGf s)
(3ChdgG (B:s
(3cd YOO JQjO Cf JLYdg ai habg aCNQL ChdkG RchJg Ke aQbg CLRGA s
(3BNQgG (B:s
(3hbO jedC eNeSkG NGdj GdhSW HCf jYO cd SJjf HhGMO hjhVY GdcSQ hROfG GdSJ ai (B30 s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
(3eUOQ GbJfGA GdCUd (B:s
(3BjI Gddg GdMcje GdYGeI (B_ (3GdfLa (B(1095) s
Keywords: (3GdeLGejYs